UNLOCKING FLUENCY: THE ROLE OF FEEDBACK IN INTENSIVE LANGUAGE LEARNING (Modern education and development, 2025)
This article explores the critical role of feedback in intensive language learning environments. It highlights how timely, personalized, and constructive feedback accelerates language acquisition, fosters learner autonomy, and enhances student motivation. The article also discusses practical strategies for educators to optimize feedback in high-intensity instructional settings.